Comparative Analysis of The Mobile Application for Marking Digital Photos in The Android and IOS Operating Systems - Paweł KACZMAREK; Rafał SZADKOWSKI; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
The paper compares native mobile applications for Android and iOS operating systems on the example of a system for watermarking digital photos. Based on this service and two-factor authentication, the similarities and differences between these platforms were discussed. The authors developed conclusions from the practical implementation and publication of two applications for the two most popular platforms used by mobile devices.
Keywords: Mobile Development; Mobile Devices; Mobile Security; Android and IOS Comparison.